2018
DOI: 10.2174/0929866525666180806110928
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Activity of Bursal Pentapeptide-(III-V) in Mice Immunized with the H9N2 Avian Influenza Vaccine

Abstract: In summary, BPP-IV did not have an effect on specific immune responses, therefore it could not reduce pathological damage in mice lungs; BPP-III provided resistance to the antigen through the cell-mediated immune response; BPP-V enhanced both humoral and cellular immune responses, therefore provided protections against the H9N2 Avian Influenza Virus (AIV). Altogether, BPP-III and BPP-V could be adjuvant candidates for the H9N2 avian influenza vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…A conserved amino sequence containing both T and B cell epitopes of the H9N2 AIV haemagglutinin (HA) protein (GNCVVQCQTERGGLN) was first selected as the antigen epitope by immunoinformatics analysis, and the epitope peptide was then conjugated to appropriate adjuvants to enhance the immune response by the transfer and controlled release of antigens (35). Our previous studies have shown that BPP-V and BP-IV can be used as immune adjuvants in combination with the commercial H9N2 AIV inactivated vaccine to enhance humoral and cellular immune responses (17,18). Therefore, BPP-V and BP-IV were conjugated to synthesize the BPP-V and BP-IV epitope peptides.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A conserved amino sequence containing both T and B cell epitopes of the H9N2 AIV haemagglutinin (HA) protein (GNCVVQCQTERGGLN) was first selected as the antigen epitope by immunoinformatics analysis, and the epitope peptide was then conjugated to appropriate adjuvants to enhance the immune response by the transfer and controlled release of antigens (35). Our previous studies have shown that BPP-V and BP-IV can be used as immune adjuvants in combination with the commercial H9N2 AIV inactivated vaccine to enhance humoral and cellular immune responses (17,18). Therefore, BPP-V and BP-IV were conjugated to synthesize the BPP-V and BP-IV epitope peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse serum samples were collected through tail vein from each group on days 1, 3,5,7,9,11,13,15,17,19,21,23,25,27, and 29 after immunization, and the anti-HA (IgG) antibody were determined to evaluate whether the mice consistently produce antibody. On days 7, 14, and 21 after immunization, mice serum samples were also collected through tail vein, and anti-HA antibody (IgG), IgG1, and IgG2a levels were determined by ELISA as previously described (22).…”
Section: Detection Of Specific Antibodiesmentioning
confidence: 99%
See 3 more Smart Citations